Proses Pembelajaran Rebana Qasidah di Sanggar Abi Aggi Kota Cilegon - Indrawan, Indrawan; Suhaya, Suhaya; Hadiyatno, Hadiyatno (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2023)
This study aims to describe how the learning process of tambourine qasidah in the Abi Aggi Studio, Cilegon City. The subjects of this study were the trainers and members of the Abi Aggi studio, Cilegon City. This research use desciptive qualitative approach. Data collection techniques used are interviews, observation and documentation. The results of the study found that the learning process of rabana qasidah in the Abi Aggi studio, Cilegon City was marked by the existence of educational interactions that occurred. This interaction is rooted in the teaching staff and learning does not occur suddenly, but proceeds through certain stages. The stages of learning activities are arranged systematically through the stages of design, implementation and evaluation. The results of learning the percussion pattern of the tambourine qasidah at the Abi Aggi studio, Cilegon City, can be concluded that the trainers and members of the studio at the Abi Aggi Studio, Cilegon City agree with the learning process implemented in the studio which can improve the ability to play the rabana qasidah instrument and is able to increase self-confidence.